MODEL PARTISIPASI MASYARAKAT DALAM MENDUKUNG EFISIENSI DAN KEEFEKTIFAN MANAJEMEN PELAYANAN PENDIDIKAN DASAR - Armidah, Armidah (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
Program efficiency and effectiveness of service management education is directed to strengthen the management of educational services, including through the efforts of increasing public participation in the development of education and setting up systems or management education funding that could increase the contribution towards the implementation of the educational process. One program efficiency and effectiveness of educational services management in addition to policy advocacy and dissemination of development education, is to increase community participation in education development. In this regard, the discussion in this module efficiency and management effectiveness of basic education services are directed at community participation in the implementation of the educational process.Key words: community partisipant, financial management, elementary education